THE EFFECT OF DIGITAL TECHNOLOGY THE EFFECT OF DIGITAL TECHNOLOGY IMPLEMENTATION ON THE UNDERSTANDING OF DIGITAL LITERACY IN THE KELUARGA YATIM MUHAMMADIYAH ORPHANAGE: PENGARUH IMPLEMENTASI TEKNOLOGI DIGITAL TERHADAP PEMAHAMAN LITERASI DIGITAL DI PANTI ASUHAN KELUARGA YATIM MUHAMMADIYAH - Nursafitri, Rike; Regita Ananda, Anggi; Ni'matul Munawaroh, Alfiyah; Nabila Khoirunisa, Rindy; Chasanah, Umi (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
This study aims to determine the effect of digital technology implementation on the understanding of digital literacy in the Muhammadiyah Orphanage by conducting digital literacy research through community service activities HMP Informatics Engineering Education. This activity positively impacts the Muhammadiyah Orphanage on understanding digital literacy. In digital technology learning activities, several types of material are delivered about graphic design and Microsoft Office applications. This type of material is considered to be able to help Muhammadiyah Orphanage Children to improve their skills and abilities in Microsoft Office and graphic design. This type of research is quantitative research with a pre-experimental design method type one group pre-test, namely orphanage children class XI-1 (11-1)) SMK as an experimental class. The data collection method used is the questionnaire and test method (pretest and posttest). Data obtained through quantitative data trials. This quantitative data is in the form of a score to determine the effectiveness of the digital technology learning process. The results of this study were able to understand the function of the main menu in graphic design and Microsoft Office. Therefore, it can improve and encourage students to understand digital literacy as evidenced by the average answer to each question that has been learned during learning activities.